PEMANFAATAN WEBGIS UNTUK LAYANAN MASJID IKHWANUL MUSLIMIN KELURAHAN AIR TAWAR BARAT - ilham yuhanda; Arie Yulfa (JURNAL BUANA, 2021)
The purpose of this research is (1) to identify the functions needed in the creation of a WebGIS system for the services of the Ikhwanul Muslimin mosque. (2) Analyze the use of waterfall methods in WebGIS development. System development techniques used are Waterfall method with stages of engineering system, analysis system, design system, evaluation system, operation and maintenance system. The result of this research is (1) identification of the functions needed in the creation of WebGIS which includes data security, data management (input, edit, delete), and a system that is able to provide a liaison between the community of the mosque environment and mosque officials . (2) WebGIS development of Ikhwanul Muslimin mosque services is built using waterfall system of development, stages include engineering system, analysis system, design system, implementation system, evaluation, and operation system. Of all these stages have successfully built a Web GIS mosque service environment with a domain address https://p3r0j3ctd.000webhostapp.com . This development has been done system evaluation test, the majority of respondents are satisfied with the work of the system and can be an alternative in the processing of mosque assistance data online as well as the publication of the distribution of mosque beneficiaries to the public.